A dynamic view of coach transformational leadership: How leadership perceptions relate to task cohesion and team potency. (November 2020) - Baird, Noelle; Martin, Luc J.; Benson, Alex J.
Abstract: We examined whether athletes' perceptions of coach transformational leadership across time related to task cohesion and team potency beliefs. Across multiple time points, we collected 384 observations ( M  = 5.41 observations per athlete) from competitive youth athletes via a mobile application designed to examine team dynamics. Multilevel structural equation modelling revealed intraindividual variation in athletes' evaluations of coach transformational leadership across time. Further, we observed robust support for a positive relation between perceptions of coach transformational leadership and task cohesion over time at both the between- and within-person levels. The relation between coach transformational leadership and team potency was significant at the between-person level, however, we did not find support for this relation at the within-person level. These results provide insight into how the ebb and flow of coach transformational leadership over time connects to team cohesion, highlighting the need for more intensive longitudinal designs that capture the dynamic nature of leadership. Highlights: We collected 384 weekly observations with an average of 5.41 responses per athlete. Athletes' perceptions of coach transformational leadership (TFL) varied across time. TFL positively related to task cohesion at both the within- and between-person level. TFL positively related to team potency at the between-person level.